Application of Gastroscopy in the Diagnosis of Congenital Pyriform Sinus Fistula in Children - Wang, Shengcai; Mei, Lin; Li, Yanzhen; Zhang, Xuexi; Zhang, Jie; Ge, Wentong; Guo, Yongli; Yu, Yongbo; Wang, Guoli; Mei, Tianlu; Liu, Qiaoyin; Sun, Nian; et al. (Frontiers in Pediatrics, 2021)
Objective: To explore the diagnostic value of gastroscopy under local anesthesia for congenital pyriform sinus fistula (CPSF). Methods: This research was a diagnostic study. Patients were received gastroscopy under local anesthesia to diagnose CPSF, and suspension laryngoscopy under general anesthesia was performed 2 days after gastroscopy. Various conditions of the internal opening of CPSF were then recorded. Patients were grouped according to lesion sides, age,time after the inflammation subsided and the history of previous surgery. The sensitivity, specificity, the area under receiver operating characteristic curve (AUC), accuracy, positive and negative predictive values of gastroscopy were compared between groups. Results: A total of 48 patients were enrolled in this study and no patients had severe gastroscopy-related complications. The diagnostic results of 41 cases (85.4%) were consistent between gastroscopy and suspension laryngoscopy. the sensitivity of gastroscopy was 86.4%, the specificity was 75%, the AUC was 0.807, the positive prediction rate was 97.4%, the negative prediction rate was 33.3%, the accuracy rate was 85.4%, and the diagnostic odds ratio (DOR) was 2.1. The kappa consistency test results had statistical significance (P=0.0026, kappa=0.3913). The diagnostic value of gastroscopy was better for the patients that inflammation subside more than 4 weeks. (P<0.0001). Conclusion: Gastroscopy under local anesthesia is a safe, effective, reliable and novel diagnostic method for CPSF, and it is especially recommended as a diagnostic method of CPSF more than 4 weeks after the inflammation subsided.